Trust and performance in business teams: a meta-analysis. Issue 5 (15th July 2020) - Morrissette, Amy M.; Kisamore, Jennifer L.
Abstract : Purpose: The purpose of this study is two-fold. First, the nature of the relationship between team trust and team performance in the business context is determined. Second, both team design (team size and team type) and methodological moderators (source of criterion measure and study date) of the relationship are assessed. Design/methodology/approach: A random-effects meta-analysis was performed on published and unpublished empirical studies. Subgroup moderator analyses were conducted using Cochran's Q. Continuous moderator analyses were conducted using meta-regression. Findings: Data from 55 independent studies (3, 671 teams) were pooled. Results indicated a large, positive relationship between team trust and team performance in real business teams. Further analyses indicated that the relationship was significantly moderated by business team type, team size and source of criterion measure. Research limitations/implications: Results indicate that different team types, sizes and performance criteria should not be treated as equivalent. Results are based on cross-sectional research and can only be generalized to business teams. Practical implications: Managers should be attentive to trust issues in work teams, as they may portend future performance problems or mirror other organizational issues that affect team performance. Team function and size predict how team trust is related to team performance. Originality/value: The present study answers a call by Costa et al. (2018) for additional investigation of moderators of the trust-performance relationship in teams using a quantitative review of studies.